A STUDY ON LEVEL OF KNOWLEDGE, PRACTICE OF PREVENTION AND STIGMA AMONG HOUSEHOLD CONTACTS OF PULMONARY TUBERCULOSIS PATIENTS ON DOTS CHEMOTHERAPY IN INDIA: A CROSS-SECTIONAL STUDY - Praveen, Vijaiyalakshimi; Rajaram, Arulmozhi; Balamurugan, Padma Praba; R, Rajkamal (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Studies on patients with tuberculosis (TB) have shown that their response to symptoms is culturally inclined. Early detection coupled with incorporation of patient health perceptions can refine tuberculosis control plans to enhance patient identification, diagnosis, and treatment outcomes. Purpose: To find out the level of knowledge, practice of prevention of tuberculosis and associated stigma among contacts from the same household of pulmonary tuberculosis patients on DOTS chemotherapy. Methods: This study is a cross-sectional one. IEC was obtained approved before starting this study. The research was conducted with 220 family contacts (aged 12 and above) using a survey. Results: Study subject’s awareness on the contagiousness of the disease (45.4%) and the seriousness of the infection (47.8%) was found to be very low. It is worrying to find that only 20% of study subjects were aware of the cause of disease (21.8% - germs). Constitutional weakness (14.5% - low immunity) was almost not considered as a risk factor. Half of the contacts (53.2%) felt they wouldn’t tell others about the illness as they would be looked down upon (56.4%). Conclusion: The lacuna in the National Tuberculosis Elimination Programme (NTEP) is that it didn’t transmit the understanding about the disease to all the affected and their immediate family. The tuberculosis disease report, along with psychological and medical support and chemotherapy, will ensure consistency and achieve the sustainable development goal of